Mucosa-associated lymphatic tissue of the vermiform appendix in appendicitis - Yu. I. Popovуch; O. A. Hryhorieva; M. L. Tavroh; O. R. Ivantsіv; N. R. Popovych (Patologìâ)
Aim. To analyze the literature on the features of the restructuring of mucosa-associated lymphatic tissue of the vermiform appendix in appendicitis.